2017
DOI: 10.1186/s12199-017-0614-y
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ willingness to care for patients infected with HIV or Hepatitis B / C in Vietnam

Abstract: ObjectivesThis study examined the factors associated with nurses’ willingness to care for patients infected with human immunodeficiency virus (HIV) or hepatitis B or C virus (HBV/HCV) in Vietnam.MethodsA cross-section of 400 Vietnamese nurses from two hospitals were selected using stratified random sampling, to whom a self-administered questionnaire was administered which included demographic items, previous experience with patients infected with HIV or HBV/HCV, and their attitudes toward these patients. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…Asia and North America were best represented by the literature, in contrast to Africa from where we identified only two published studies, both set in Ghana ( Table 1 ). Among the 19 studies that used a quantitative study design, eight used a convenient sampling method which introduces selection bias 33 35 , 37 , 45 , 51 , 59 , 62 , two studies did not describe a sampling method 39 , 58 , five used a random sampling method 36 , 46 , 47 , 50 , 61 , three studies included all intended participants 44 , 49 , 52 , and only one study used a sample size based on pre-study consideration 47 . A participant response rate was presented in 10 studies; in nine of these the response rate was >60% 35 37 , 45 , 49 52 , 59 and one had a 30% response rate 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Asia and North America were best represented by the literature, in contrast to Africa from where we identified only two published studies, both set in Ghana ( Table 1 ). Among the 19 studies that used a quantitative study design, eight used a convenient sampling method which introduces selection bias 33 35 , 37 , 45 , 51 , 59 , 62 , two studies did not describe a sampling method 39 , 58 , five used a random sampling method 36 , 46 , 47 , 50 , 61 , three studies included all intended participants 44 , 49 , 52 , and only one study used a sample size based on pre-study consideration 47 . A participant response rate was presented in 10 studies; in nine of these the response rate was >60% 35 37 , 45 , 49 52 , 59 and one had a 30% response rate 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 65.8% in the Vietnam and 79% of participants in the Japan studies don't care of acquiring these infections from infected collogues. Again in the Japan study 88% of the participants disagree and strongly disagreed to avoid infected colleagues (13,18,22). This discrepancy may be due to lack of personal protective equipment and nurse's attitude for colleagues may be different for other patients.…”
Section: Discussionmentioning
confidence: 92%
“…However, the nding in this study is much lower than the study from Vietnam that reported 73.3% of the respondents to be willing to care for hepatitis B/C patients. Besides, in a study from Japan only 18% of nurses agreed or somewhat agreed as they were unwilling to care for these patients (13,18). The possible reason for this difference may be lack of preventive and therapeutic facilities in hospitals that imposes fear of acquiring these infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations